2022
DOI: 10.3390/app122211810
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Coal Specimens Subjected to Uniaxial Cyclic Loading and Unloading

Abstract: The paper represents a test investigation of the mechanical properties and acoustic emission (AE) characteristics of low-strength coal specimens subjected to cyclic loading and unloading. From the lab tests, the following conclusions can be obtained: (1) The axial strain is very well linear with the loading–unloading cycle number, and the circumferential and volumetric strains are approximately quadratic functions with the loading–unloading cycle number; (2) Under the same loading stress interval, the elastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The mechanical properties of rock (masses) will be different depending on the stress environment. Scholars have conducted indoor mechanical tests on various types of rocks (masses) under complex stress environments and these can be roughly divided into loading mechanical, unloading mechanical [2], cyclic loading and unloading mechanical [3][4][5][6][7], and damage reloading mechanical tests [8][9][10]. Previous studies [11][12][13] conducted indoor loading tests and studied the stress-strain curves, deformation, and failure characteristics of sandstone and conglomerate specimens under various confining pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of rock (masses) will be different depending on the stress environment. Scholars have conducted indoor mechanical tests on various types of rocks (masses) under complex stress environments and these can be roughly divided into loading mechanical, unloading mechanical [2], cyclic loading and unloading mechanical [3][4][5][6][7], and damage reloading mechanical tests [8][9][10]. Previous studies [11][12][13] conducted indoor loading tests and studied the stress-strain curves, deformation, and failure characteristics of sandstone and conglomerate specimens under various confining pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Tang, J. et al [15] found that under cyclic loading and unloading, the AE characteristics of rock fracture show a clear Kaiser effect, and the Felicity effect is significantly observed when the loading force reaches 70% of the peak value. The b-value is commonly used, based on AE, to predict the precursors of rock failure, and a significant increase or decrease in the b-value suggests that the rock may have a large number of cracks or is about to become unstable and fail [16][17][18]. Under low stress conditions, b-value activity is weak and almost imperceptible, while under high stress states, b-value activity is intense.…”
Section: Introductionmentioning
confidence: 99%
“…When a load or force is applied to a soil, its particles reorganize and compress [26,27], which can lead to microfractures or internal displacements [28] in the material that will release energy in the form of acoustic waves [29]. When these emissions are monitored, valuable information can be obtained about the evolution of soil deformation [28,30], changes in mechanical behavior [31,32], the location and propagation of microfractures [33], the presence of weaknesses or potentially unstable areas (of great importance for the safety assessment of structures built on the ground) [20], and, in general, the strength of the soil [29,34] to applied forces. Acoustic characteristics may vary according to the soil properties [33], applied load [13,26], and other factors [31], so specific equipment and knowledge [35], as well as a careful approach, are needed in each particular case.…”
Section: Introductionmentioning
confidence: 99%